Optimalisasi dan Pemanfaatan Website Desa dalam Akselerasi Peningkatan Ekonomi Masyarakat dan Potensi Desa Mario - Andi Sumangelipu; Muzakkir; Syahida; Zainatul Afiat; Sinaria (Compile Journal of Society Service, 2025)
According to 2022 data from the Central Statistics Agency (BPS), approximately 70% of villages in Indonesia still have limited access to adequate information. A website makes information about business opportunities, superior products, and public services more easily accessible to the public. Mario Village, Tanasitolo District, Wajo Regency, already has its own website through government support, but community access and utilization of the village website for economic development are still suboptimal. This community service program aims to raise public awareness of the importance of optimizing and utilizing village websites to accelerate economic growth and village potential. This community service activity takes the form of outreach and counseling for local residents and village website managers. This outreach program increases community understanding of the importance of utilizing village websites for economic development and provides insight into village website management for website managers